Cysteine-rich protein-templated silver nanoclusters as a fluorometric probe for mercury(ii) detection. Issue 6 (23rd January 2019) - Zhou, Yongquan; Wang, Jinjie; Yang, Guang; Ma, Shuyi; Zhang, Min; Yang, Jingxia
Abstract : In this paper, we explored a convenient method for preparing stable silver nanoclusters (AgNCs) within 1 h at room temperature using keratin as a template and NaBH4 as a reducing agent. Abstract : In this paper, we explored a convenient method for preparing stable silver nanoclusters (AgNCs) within 1 h at room temperature using keratin as a template and NaBH4 as a reducing agent. As a group of cysteine-rich structural proteins, keratins are abundant in wool, hair and feathers. The prepared AgNCs exhibited high fluorescence intensity and stable emission at 705 nm. Their fluorescence intensity decreased by <20% after 3 months of storage in the dark at 4 °C. The AgNCs were then used to detect Hg 2+ ions with high selectivity. The detection limit can be low (6.5 nM), and the linear range was from 13.7 nM to 10 μM. Furthermore, the mechanism of the interaction of AgNCs with Hg 2+ ions was studied using various analytical techniques, such as UV-vis, XRD, TEM and XPS.